Manuel do Vale de Moura (1564–1650) e o Pensamento Demonológico e Religioso Português: o De Ensalmis na Europa de Seiscentos - Miguel Oliveira da Costa Peixe, João (Revista Vozes dos Vales: Publicações Acadêmicas, 2015)
In 1620, Manuel do Vale de Moura, a deputy of the Inquisition in Évora, published a book entitled *De Incantationibus seu Ensalmis*. In over five hundred pages written in Latin, the work exhaustively analyzes popular healing practices considered superstitious. In his effort to define and characterize such acts, Vale de Moura has the opportunity to reflect on other related themes, such as pacts and demonic intervention, magic, prophecy, vain observances, and, to a lesser extent, astrology. With such a broad field of interest, the book decisively contributes to a better understanding of the mentality of the time in the realm of the supernatural. This article presents a synoptic overview of the author's doctoral research, which aims at the complete translation of the work and, based on it, defining Portuguese demonological and religious thought of the early 17th century.
Keywords: Religion; Demonology; Magic; Enchantments; Inquisition; Manuel do Vale de Moura